An organic–inorganic hybrid zinc phosphite framework with room temperature phosphorescence. Issue 30 (26th March 2018) - Ni, Ai-Yun; Mu, Ying; Pan, Jie; Han, Song-De; Shang, Meng-Meng; Wang, Guo-Ming
Abstract : An organic–inorganic hybrid zinc phosphite framework with large channels and fascinating room temperature phosphorescence has been presented. Abstract : A novel room temperature phosphorescent material has been developed by the use of luminescent organic rigid poly-imidazole moieties coordinating to a zinc phosphite framework, which shows excellent thermal and mechanical stability.